2021
DOI: 10.1038/s41598-021-89977-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necroptosis is correlated with a favorable immune cell signature and programmed death-ligand 1 expression in cholangiocarcinoma

Abstract: Necroptosis, a regulated form of necrosis, has emerged as a novel therapeutic strategy that could enhance cancer immunotherapy. However, its role in tumorigenesis is still debated because recent studies have reported both anti- and pro-tumoral effects. Here, we aimed to systematically evaluate the associations between tumor necroptosis (mixed lineage kinase domain-like protein, MLKL; phosphorylated MLKL, pMLKL; and receptor-interacting protein kinase 1–receptor-interacting protein kinase 3, RIPK1–RIPK3 interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…In both cohorts, an increasing level of immunoreaction score of RIPK1, RIPK3 and MLKL-p resulted in an increasing level of intratumoral density of CD3 + and CD8 + T-lymphocytes (figure 5A and figure S4 in online supplemental file 1), enforcing the immunogenic role of NCP in cancer, 28 as also previously shown in breast cancer 29 and, recently, in cholangiocarcinoma. 30 NCS, as well as tumor-infiltrating CD8 + T cells, showed also prognostic relevance in terms of OS, while TILs were not found associated with a worse prognosis in both Italian and Japanese cohorts (figure 5B with table 3 and figure S6 with table S5 in online supplemental file 1 for NCS; figure S7 with table S7 in online supplemental file 1 for CD8 + T cells and TILs). These results were also confirmed in TCGA-LIHC data considering NCS as a combined mRNA expression score of the three receptors and the inferred CD8 + T cells infiltration from RNAseq data through deconvolution approaches (figure S9 and table S8 in online supplemental file 1).…”
Section: Discussionmentioning
confidence: 94%
“…In both cohorts, an increasing level of immunoreaction score of RIPK1, RIPK3 and MLKL-p resulted in an increasing level of intratumoral density of CD3 + and CD8 + T-lymphocytes (figure 5A and figure S4 in online supplemental file 1), enforcing the immunogenic role of NCP in cancer, 28 as also previously shown in breast cancer 29 and, recently, in cholangiocarcinoma. 30 NCS, as well as tumor-infiltrating CD8 + T cells, showed also prognostic relevance in terms of OS, while TILs were not found associated with a worse prognosis in both Italian and Japanese cohorts (figure 5B with table 3 and figure S6 with table S5 in online supplemental file 1 for NCS; figure S7 with table S7 in online supplemental file 1 for CD8 + T cells and TILs). These results were also confirmed in TCGA-LIHC data considering NCS as a combined mRNA expression score of the three receptors and the inferred CD8 + T cells infiltration from RNAseq data through deconvolution approaches (figure S9 and table S8 in online supplemental file 1).…”
Section: Discussionmentioning
confidence: 94%
“…Studies by Lomphithak et al. have shown that in cholangiocarcinoma, necroptosis is associated with a favorable immune cell signature ( 32 ). In addition, inflammation can also regulate necroptosis through cytokines such as IFN, increasing the expression of MLKL.…”
Section: Discussionmentioning
confidence: 99%
“…necroptosis can either promote or reduce tumor growth depending on the type of cancer. For example, reduced expression of necroptotic markers promote tumor growth in breast cancer (Stoll et al, 2017) and acute myeloid leukemia (Höckendorf et al, 2016), whereas in pancreatic ductal adenocarcinoma (Seifert et al, 2016) and cholangiocarcinoma (Lomphithak et al, 2021) increased expression of necroptosis markers are associated with tumor growth. Because aging is a slow and gradual process, further studies with long-term Nec-1s treatment will be needed to address the feasibility of using necroptosis inhibitor(s) for inflammaging and aging.…”
Section: Discussionmentioning
confidence: 99%